Effects of Clopidogrel, Prasugrel and Ticagrelor on Microvascular Function and Platelet Reactivity in Patients With Acute Coronary Syndrome Undergoing Coronary Artery Stenting. A Randomized, Blinded, Parallel Group Trial - Schnorbus, Boris; Jurk, Kerstin; Lackner, Karl J.; Welk, Caroline; Münzel, Thomas; Gori, Tommaso (Frontiers in Cardiovascular Medicine, 2021)
Aims: In this pre-specified analysis of the “endothelium, stent and antiplatelet therapy” study, we investigate the impact of antiplatelet therapies on microvascular function in patients undergoing stenting for an acute coronary syndrome. Methods and results Fifty-six patients (age: 63[55-67] years, males, 10 diabetics, 27 non-ST-elevation myocardial infarction) were randomized to receive clopidogrel, ticagrelor or prasugrel in form of oral loading 2 hours before stenting followed by oral therapy. Investigators were blinded to the allocation. Laser-Doppler microvascular function and ADP-induced platelet aggregation capacity were measured at baseline, 2 hours after oral antiplatelet loading, and 1 day, 1 week and 1 month after stenting during chronic therapy with the same antiplatelet agent. Platelet aggregation decreased in all groups 2 hours after oral loading, with a significantly larger effect in the prasugrel group (P=0.009). Similarly, prasugrel and ticagrelor loading was followed by an increase in microvascular reactive hyperemia (P=0.007 and P=0.042 compared to clopidogrel). This effect disappeared one day after coronary intervention, with a significant decrease in the prasugrel group (P=0.026). Similarly, analysis of microvascular conductance showed a larger increase in the prasugrel group 2 hours after loading (P=0.022 among groups), and a decrease in all groups after stenting. Conclusions Oral loading with prasugrel (and less consistently ticagrelor) is associated with improved microvascular function and stronger platelet inhibition in acute coronary syndrome patients. This effect was however lost 1 day after stenting and during subsequent follow-up. Further studies are necessary to clarify the the long-term effects and potential benefits of P2Y12 inhibitors on microvascular damage